Tax Evasion of Buying and Selling Land by Notary - Purnama Aji, Pradistya; Salsabila Khairunnisa; Tessalonika Kusuma Dewi; Oktavian Dimas Widiarto (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2024)
Tax evasion in land sale and purchase transactions by notaries is a significant legal problem, especially because of the strategic role of notaries in ensuring legal certainty. This study aims to analyze the application of criminal sanctions against notaries involved in tax evasion, particularly in the Denpasar District Court decision number 300/PID.B/2015 / PN.DPS. The method used in this study is normative juridical, with a case study approach to evaluate the relevant legal aspects and the implementation of criminal sanctions in this context. This writing includes a descriptive type of legal analysis with reference to related legislation, such as the Notary Office Act, the Criminal Code, and related documents and literature. The results showed that the notary has the authority to manage taxes such as Income Tax and Customs acquisition of land and building rights. However, this authority can be abused, as happened in the case of notaries with us initials. In such cases, judges pass a verdict under Article 372 of the Criminal Code, which is considered relevant for the criminal offense of embezzlement. This study recommends increased supervision, reform of tax policies related to notaries, as well as improving the integrity of the profession through strengthening the code of ethics. This effort is expected to increase public confidence in notaries and the legal system in Indonesia.